Designing Supply Chain Management (SCM) Strategies To Reduce Operational Risks At PT. Mitra Tirta Andalan - Muhamad Hanafii Afnan; Dessy Isfianadewi (International Journal of Economics, Business and Innovation Research, 2025)
PT Mitra Tirta Andalan is a trading company specializing in cast metal products using a Make-To-Order (MTO) approach. The company collaborates with several production partners to meet customer demands. However, it faces two key challenges: delays in production schedules from partners causing late deliveries, and machinery or facility breakdowns at partner companies. This study aims to develop a Supply Chain Management (SCM) strategy to address these operational risks. One key solution is supplier diversification and a more structured supplier selection process. This approach helps the company reduce dependency on a single partner and enhances flexibility in dealing with production challenges. The findings reveal that supplier diversification improves operational continuity, maintains customer satisfaction, and strengthens the company’s position within the supply chain. Recommendations include adding new supplier partnerships, optimizing digital marketing strategies, and expanding product offerings to support future business growth.